1996
DOI: 10.1088/0953-8984/8/33/006
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of the Poynting vector and the dispersion surface in the absorbing crystal

Abstract: The relationship of the Poynting vector and the dispersion surface in the absorbing crystal is studied in detail. It is found that the long-accepted concept in which the physical energy flow of waves in the absorbing crystal is normal to the real part of the dispersion surface is not valid when the contribution of the imaginary part of the atomic scattering factor to the diffraction is comparable to that of the real part.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…In our previous work [1], we found that, in the symmetrical Laue case, when the contribution of the imaginary part of the atomic scattering factor to the diffraction is comparable to that of the real part near the absorption edge, the direction Poynting vector within the crystal deviates from the normal of the real part of the complex dispersion surface. As we know, the diffraction and the dispersion surface in the Bragg case are quite different from those in the Laue case.…”
mentioning
confidence: 85%
See 3 more Smart Citations
“…In our previous work [1], we found that, in the symmetrical Laue case, when the contribution of the imaginary part of the atomic scattering factor to the diffraction is comparable to that of the real part near the absorption edge, the direction Poynting vector within the crystal deviates from the normal of the real part of the complex dispersion surface. As we know, the diffraction and the dispersion surface in the Bragg case are quite different from those in the Laue case.…”
mentioning
confidence: 85%
“…So we address the question of whether the above-mentioned relationship is valid or not in the symmetrical Bragg case, which is the purpose of this letter. The notation is the same as in reference [1].…”
mentioning
confidence: 99%
See 2 more Smart Citations